Mathematics Standard Level for the IB Diploma - Paul Fannon; Vesna Kadelburg; Ben Woolley; Stephen Ward (Cambridge, United Kingdom Cambridge University Press, 2012)
This title forms part of the completely new Mathematics for the IB Diploma series. This highly illustrated coursebook, available in both print and e-book formats, has been written to specifically cover the new IB Standard Level syllabus. Based on the new group 5 aims, the progressive approach encourages cumulative learning. Features include: a dedicated chapter exclusively for combined exercises; plenty of worked examples; questions colour-coded according to grade; exam-style questions; feature boxes of hints and tips. The print book includes a CD-ROM providing a complete e-version of the book, extension worksheets, prior learning sheets, calculator skills sheets and fill-in proofs. These additional materials are also included in the e-book version.
Keywords: IBDP-Group-5